Characterization of Segureña sheep production systems in the area of Sierra deI Segura y la Sagra, Spain - Navarro-Ríos M.J.; Marín-Bernal A.M.; Martí A.; Fernández C. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
The aim of this study is to present the basic characteristics which define the sheep systems in some zones of the PGI Cordero de Segura y la Sagra protected area, in order to bring about actions to improve the competitiveness of such systems. A survey has been conducted among 93 farm owners. The questionnaire included questions regarding herd characteristics, age, educational level, workers, and continuity of the farm activity. The average herd size is 378 animals and the Segureña breed sheep is predominant (99 percent). In 93.5 percent of cases the owner works full time on the farm and the main economic benefit is the sale of lambs for meat, but only 9.7 percent of farmers belong to some kind of marketing cooperative. The average farmer's age is 50 years old and a high percentage (87.1 percent) has no education or a very basic one. The year work unit (YWU) is 1.31 and the work is mainly of family type. In only 12 percent of the cases the continuity of the activity is assured. The above analysed aspects show that it is necessary to achieve better socioeconomic conditions of farms. The PGI Cordero de Segura y la Sagra could be useful to improve these aspects. Therefore we suggest that the PGI must be promoted among farmers, especially among young people.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)